Damage analysis of carbon/epoxy plates after drilling - Durão, Luís M. (2014)
Drilling of composites plates normally uses traditional techniques but damage risk is high. NDT use is important. Damage in a carbon/epoxy plate is evaluated by enhanced X-rays. Four different drills are used. The images are analysed using Computational Vision techniques. Surface roughness is compared. Results suggest strategies for delamination reduction.